2022
DOI: 10.3390/insects13080688
|View full text |Cite
|
Sign up to set email alerts
|

Live Drosophila melanogaster Larvae Deter Oviposition by Drosophila suzukii

Abstract: The worldwide invasive insect pest, Drosophila suzukii Matsumura (spotted-wing Drosophila), lays eggs in soft and stone fruit before harvest. Hatched larvae cause fruit collapse and significant economic losses. Current control methods rely primarily on foliar insecticide applications, which are not sustainable long-term solutions due to regulatory restrictions and the risk of insecticide resistance developing. We showed before that D. suzukii were deterred from laying eggs on artificial media previously visite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 51 publications
0
12
1
Order By: Relevance
“…Previous visitation on a food source by other Drosophila species, such as D. melanogaster or Drosophila lutescens (Malloch) prior to the introduction of D. suzukii have consistently led to fewer eggs laid by D. suzukii compared to egg laying on control media not exposed to non‐ D. suzukii species 46,47 . Comparable results were shown by Kienzle and Rohlfs where D. suzukii deposited significantly fewer eggs on blueberries previously oviposited on by D. melanogaster or wounded, indicating the presence of heterospecific cues by non‐ D. suzukii Drosophila species, compared to intact and untouched blueberries that had never been visited by any flies 48 .…”
Section: Interactions Between D Suzukii and Other Drosophila Species ...mentioning
confidence: 89%
See 4 more Smart Citations
“…Previous visitation on a food source by other Drosophila species, such as D. melanogaster or Drosophila lutescens (Malloch) prior to the introduction of D. suzukii have consistently led to fewer eggs laid by D. suzukii compared to egg laying on control media not exposed to non‐ D. suzukii species 46,47 . Comparable results were shown by Kienzle and Rohlfs where D. suzukii deposited significantly fewer eggs on blueberries previously oviposited on by D. melanogaster or wounded, indicating the presence of heterospecific cues by non‐ D. suzukii Drosophila species, compared to intact and untouched blueberries that had never been visited by any flies 48 .…”
Section: Interactions Between D Suzukii and Other Drosophila Species ...mentioning
confidence: 89%
“…The role of CHCs in interspecific interactions between D. suzukii and other Drosophila species is an area worthy of further investigation. A recent paper showed that presence of live D. melanogaster larvae led to reduced egg laying by D. suzukii but there was no evidence for the involvement of CHCs in this 47 …”
Section: Drosophila Cuticular Hydrocarbons and Their Role In Interspe...mentioning
confidence: 93%
See 3 more Smart Citations